Effective absorption coefficient of a graphene atop of silicon nitride nanophotonic circuit. (December 2020) - Komrakova, S; Kovalyuk, V; An, P; Golikov, A; Rybin, M; Obraztsova, E; Goltsman, G
Abstract: In this paper, we demonstrate the results of a study of the optical absorption properties of graphene integrated with silicon nitride O-ring resonator. We fabricated an array of O-ring resonators with different graphene coverage area atop. By measuring the transmission spectra of nanophotonic devices with and without graphene, we calculated the effective absorption coefficient of the graphene on a rib silicon nitride waveguide.